(untitled) (Albayan Scientific Journal, 2023)
Microalgae breeding media must be cost-effective, enable high growth, meet exact requirements and be readily available. The effect of different levels of urea and rice wash water [25, 50 and 75%] in the growth medium on the biochemical constituents (protein, carbohydrates, lipids, fatty acids, and amino acids) of the N. oceanica was assessed compared to the F/2 Guillard standard medium. The obtained results revealed that the chemical constituents of N. oceanica were influenced by the used level of urea and rice wash water. The highest total protein, carbohydrate contents, and the maximum percentage of essential amino acids (EAA) (55.16%) were obtained by using the MF3 medium (75% RWW) as compared to the control (100% F/2). The highest total lipid content was achieved by using the MF3 medium (75% RWW) producing (41.72 %), were the obtained of highest biomass productivity and lipid productivity in MF3 medium . In accordance, the highest total saturated fatty acids percentage (TSFA) of N. oceanica was recorded by MF3 medium. However, the highest total unsaturated fatty acids percentage (USFA) was exhibited by the MF3 medium. The present study recommended taming results for aquaculture feeding by using proposed MF3 and MF2 medium as a lipid promoter and as a protein promoter.